The Taxation of Internationally Portable Pensions: Fiscal Issues and Policy Options - Bernd Genser; Robert Holzmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
Pension policy reforms across the world in recent decades are a reaction to the changing demographic and socioeconomic environment. While pension scheme redesign has received much attention, the tax treatment of contributions, returns, and benefits of retirement savings remains mostly unattended and the taxation of internationally portable pensions is terra incognita for economists. This paper focuses on the huge differences in old-age pension taxation within and across OECD countries and highlights fiscal equity and efficiency issues that emerge in a world of internationally mobile workers and pensioners. It highlights that pension taxation differs widely not only across countries but also across pension pillars within a country, creating savings and mobility distortions and fiscal equity problems at individual and country level. The paper offers explanations for this heterogeneity and proposes a switch from deferred taxation towards front-loaded taxation of retirement savings to meet the demographic challenges of a globalized world. Three policy options presented differ in the way taxes are paid, but all of them are claimed superior to single-country measures taken to uphold deferred pension taxation or to rely on renegotiations of bilateral double taxation treaties.
Keywords: H20; H24; H55; 330; income tax reform; taxation of pensions; deferred income taxation; double taxation treaties